Local Characteristics Content: An Analysis of ELT Textbook for Young Learners - Ginting, Siti Aisah (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
The purpose of this study was to analyse the media used in ELT textbook for beginners based on local characteristics of students by showing the data from analysed textbook, which is inappropriate for the the young learners in Indonesia, and this media made the teaching learning process ineffective and inefficient. Descriptive research design was applied in this study. The technique for collecting the data was quantitative approach. There were three (3) textbooks commonly used in primary level grade 4 in Indonesia. Those three were analyzed based on the local characteristics of students using demographic analysis. The result shows that only 5.6% of the media was related to local characteristics of students since the rest were to related general and foreign characteristic which reached 49% and 45.4% respectively. Therefore, the reason why the Englishlearners in Indonesia particularly on primary level grade 4 could not reach the standard of English Learning was because the media was 94.4% not related to the local characteristics of students.